Advances in urbanism, smart cities, and sustainability - Chatterjee, Uday; Mukherjee, Jenia; Majumdar, Sushobhan; Biswas, Arindam (Boca Raton: CRC Press, 2022)
'While technology is developing at a fast pace, urban planners and cities are still behind in finding effective ways to use technology to address citizen's needs. Multiple aspects of sustainable urbanism are brought together in this book along with advanced technologies and their connections to urban planning and management. It integrates urban studies, smart cities, AI, IoT, remote sensing and GIS. Highlights also land use planning, spatial planning, and ecosystem-based information to improve economic opportunities. Urban planners and engineers will understand the use of AI in disaster management and the use of GIS in finding suitable landfill sites for sustainable waste management'--
Includes bibliographical references and index.
Keywords: City planning; Smart cities -- Case studies; City planning -- Case studies; Sustainable urban development -- Case studies